Acceleration of flowering during shade avoidance in Arabidopsis alters the balance between FLOWERING LOCUS C-mediated repression and photoperiodic induction of flowering. - Wollenberg, Amanda C. (2008)
The timing of the floral transition in Arabidopsis (Arabidopsis thaliana) is influenced by a number of environmental signals. Here, we have focused on acceleration of flowering in response to vegetative shade, a condition that is perceived as a decrease in the ratio of red to far-red radiation. We have investigated the contributions of several known flowering-time pathways to this acceleration. The vernalization pathway promotes flowering in response to extended cold via transcriptional repression of the floral inhibitor FLOWERING LOCUS C (FLC); we found that a low red to far-red ratio, unlike cold treatment, lessened the effects of FLC despite continued FLC expression. A low red to far-red ratio required the photoperiod-pathway genes GIGANTEA (GI) and CONSTANS (CO) to fully accelerate flowering in long days and did not promote flowering in short days. Together, these results suggest a model in which far-red enrichment can bypass FLC-mediated late flowering by shifting the balance between FLC-mediated repression and photoperiodic induction of flowering to favor the latter. The extent of this shift was dependent upon environmental parameters, such as the length of far-red exposure. At the molecular level, we found that far-red enrichment generated a phase delay in GI expression and enhanced CO expression and activity at both dawn and dusk. Finally, our analysis of the contribution of PHYTOCHROME AND FLOWERING TIME1 (PFT1) to shade-mediated rapid flowering has led us to suggest a new model for the involvement of PFT1 in light signaling.